Glial cells: their role in behaviour - Laming, Peter R.; Sycová, Eva; Reichenbach, Andreas
Description Contents Resources Courses About the Authors In mammals the glial (or glue) cells contribute some fifty percent of the volume of the brain. In contrast to the traditional view that they have a purely physically supportive role, research in the past three decades has shown that glia interact morphologically, biochemically, and physiologically with neurons during changes in behavior. The evidence suggests that glia may modulate neuronal activity and thereby influence behavior. This is the first book that describes and discusses these neuronal-glial interactions in relation to behavior. A distinguished set of authors addresses these interactions from a number of viewpoints